Supplementing transcranial direct current stimulation to local infiltration series for refractory neuropathic craniocephalic pain: A randomized controlled pilot trial - Wandrey, Jan D.; Kastelik, Joanna; Fritzsche, Thomas; Denke, Claudia; Schäfer, Michael; Tafelski, Sascha (Frontiers in Neurology, 2023)
Background Some patients with neuralgia of cranial nerves with otherwise therapy-refractory pain respond to invasive therapy with local anaesthetics. Unfortunately, pain regularly relapses despite multimodal pain management. Transcranial direct current stimulation (tDCS) may prolong pain response due to neuro-modulatory effects. Methods This controlled clinical pilot trial randomised patients to receive anodal, cathodal or sham-tDCS stimulation prior to local anaesthetic infiltration. Pain attenuation, quality-of-life and side effects were assessed and compared with historic controls to estimate effects of tDCS stimulation setting. Results Altogether, 17 patients were randomised into three groups with different stimulation protocols. Relative reduction of pain intensity in per protocol treated patients were median 73%, 50% and 69% in anodal, cathodal and sham group, respectively (p=0.726, NNT 12 active vs. sham). Compared with a historic control group, a lower rate of responders with 50% reduction of pain intensity indicates probable placebo effects (OR 3.41 stimulation vs. non-stimulation setting, NNT 3.63). 76.9% (n=10) of tDCS patients reported mild side-effects. Of all initially included 17 patients, 23.5% (n=4) withdrew their study participation with highest proportion in the cathodal group (n=3). A sample size calculation for a confirmatory trial revealed 120 patients using conservative estimations. Discussion This pilot trial seems to suggest that series of anodal tDCS has some beneficial effect as neuro-modulatory treatment combined with series of local anaesthetic infiltrations. However, results may indicate placebo effects of tDCS and drop-out rate in this population appears high. Anodal tDCS warrants further confirmation as neuro-modulatory pain treatment option.